PENGARUH PELATIHAN, MOTIVASI, DAN KOMPENSASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA PT AGRI INDOMAS PALEMBANG - Luthfiyah, Anisah; Madjir, Sulbahri; Hakimah, Yusro (JURSIMA, 2025)
The research aims to understand and analyze the influence of Training, Motivation, and Compensation on Employee Performance through Job Satisfaction at PT Agri Indomas Palembang, both directly and indirectly. This study employs a non-probability sampling method using purposive sampling technique. Purposive sampling is the selection of samples based on certain considerations according to the desired criteria to determine the number of samples to be studied. The researcher used a sample in this study based on Slovin's formula, resulting in a sample of 49 respondents. The data analysis method used in this research is the Structural Equation Model (SEM) analysis. Hypothesis testing statistically uses SmartPLS. The results of this study indicate that Training does not have a significant effect on Job Satisfaction with a p-value of 0.060, Motivation does not have a significant effect on Job Satisfaction with a p-value of 0.539, Compensation has a significant effect on Job Satisfaction with a p-value of 0.002, Training has a positive and significant effect on Employee Performance with a p-value of 0.032, Motivation does not have a significant effect on Employee Performance with a p-value of 0.410, Compensation has a positive and significant effect on Employee Performance with a p-value of 0.042, and Job Satisfaction has a significant effect on Employee Performance with a p-value of 0.000. The Training variable has a positive and significant indirect effect on Employee Performance through Job Satisfaction with a p-value of 0.058, the Motivation variable does not have a significant indirect effect on Employee Performance through Job Satisfaction with a p-value of 0.552, and the Compensation variable has a significant indirect effect on Employee Performance through Job Satisfaction with a p-value of 0.008. Job Satisfaction does not mediate the effect of Motivation on Employee Performance but can mediate the effects of Training and Compensation on Employee Performance.